2022
DOI: 10.1016/j.amsu.2022.103260
|View full text |Cite
|
Sign up to set email alerts
|

Total mesorectal excision laparoscopic versus transanal approach for rectal cancer: A systematic review and meta-analysis

Abstract: Introduction Total mesorectal excision (TME) performed for the first time by Held through an open approach, it has become the standard technique for the surgical treatment of rectal cancer. The aim the of this meta-analysis is to compare the outcomes provided by TaTME than LaTME. Material and methods In this meta-analysis, we included all comparative studies, prospective and retrospective, which addressed in low and middle rectal cancer, a comparison between TaTME and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Its unique “downward and upward” anatomical angle avoids the “chopstick effect” resulting from space narrowing during laparoscopic surgery, particularly benign prostatic hyperplasia, pelvic narrowing, visceral fat, and/or BMI > 30 kg/m2 ( 15 ). As a current research hotspot in the field of colorectal and anal surgery, the procedure has been applied in clinical practice in many countries and a number of randomized controlled studies have been carried out ( 16 18 ), but variability in reported findings still precludes firm conclusions. Some studies found that TaTME was a procedure that was not inferior to laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Its unique “downward and upward” anatomical angle avoids the “chopstick effect” resulting from space narrowing during laparoscopic surgery, particularly benign prostatic hyperplasia, pelvic narrowing, visceral fat, and/or BMI > 30 kg/m2 ( 15 ). As a current research hotspot in the field of colorectal and anal surgery, the procedure has been applied in clinical practice in many countries and a number of randomized controlled studies have been carried out ( 16 18 ), but variability in reported findings still precludes firm conclusions. Some studies found that TaTME was a procedure that was not inferior to laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical effectiveness of TaTME was primarily compared with LaTME, which reflects the current shift from the conventional open approach to the minimally invasive laparoscopic technique. 17,20,21,26,31 Overall, the evidence regarding clinical effectiveness suggests that TaTME has lower rates of conversion 21,22 and positive CRM 17,21,25 global health-related quality of life, 18-20 mortality, 18,21,22,25 postoperative complications, 18,20-22,25 and anastomotic leakage. 21,22,24 TaTME may be cost-effective compared with open TME and LaTME.…”
Section: Conclusion and Implications For Decision-or Policy-makingmentioning
confidence: 98%
“…Subsequent systematic reviews, although based largely on non-randomised studies, showed similar short ( 47 ) and long term oncological, functional outcomes ( 48 50 ), quality of life (QoL) ( 49 ) and complications ( 47 , 50 ).…”
Section: Introductionmentioning
confidence: 99%